EDUCATIONAL MARKETING MIX INNOVATION TO INCREASE STUDENT ENTRY INTEREST - Nurhasanah, Siti; Rahayu, Puji; Sitna Hajar, Elvira (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to analyze innovations in education marketing strategies at MI Al-Wathoniyah 22 Bekasi in increasing interest in entering schools. The qualitative method used in conducting this research is qualitative. Research data collection is done through interviews, observations, and document studies. The data analysis techniques are reducing data, presenting data, and finally drawing conclusions. The results showed that MI Al-Wathoniyah 22 innovated by implementing and maximizing seven marketing mixes: products, places, prices, promotions, human resources, physical evidence, and processes. Innovation in the educational marketing mix, especially in physical evidence and process elements. The use of advanced technology in learning, the design of adequate physical facilities, and the implementation of efficient admissions procedures are examples of innovations that can increase the attractiveness of schools and improve the overall quality of education services. This will increase the interest in prospective students entering the school.